2010
DOI: 10.1186/1471-2148-10-356
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of differential gene expression on the ecological adaptation of the snail Littorina saxatilis

Abstract: BackgroundIn the past 40 years, there has been increasing acceptance that variation in levels of gene expression represents a major source of evolutionary novelty. Gene expression divergence is therefore likely to be involved in the emergence of incipient species, namely, in a context of adaptive radiation. In this study, a genome-wide expression profiling approach (cDNA-AFLP), validated by quantitative real-time polymerase chain reaction (qPCR) were used to get insights into the role of differential gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 93 publications
(113 reference statements)
0
14
0
Order By: Relevance
“…Estimates of neutral genetic diversity in this study indicate a lack of genetic structure at the various hierarchical spatial scales, although adaptive genetic diversity could still be playing a role in the recruitment process. Recent genomic studies of marine fish and molluscs have demonstrated that under strong selection pressures, adaptive variation can be maintained in marine environments despite high levels of gene flow (Galindo et al 2009;Martinez-Fernandez et al 2010;Hess et al 2013;Solas et al 2013;Milano et al 2014). Consequently, patterns of abalone larval settlement and establishment could be determined by underlying adaptive genetic variation, where recruitment at the reef scale is dependent on the settlement of compatible adaptive genotypes.…”
Section: Factors Influencing Larval Movement and Recruitmentmentioning
confidence: 99%
“…Estimates of neutral genetic diversity in this study indicate a lack of genetic structure at the various hierarchical spatial scales, although adaptive genetic diversity could still be playing a role in the recruitment process. Recent genomic studies of marine fish and molluscs have demonstrated that under strong selection pressures, adaptive variation can be maintained in marine environments despite high levels of gene flow (Galindo et al 2009;Martinez-Fernandez et al 2010;Hess et al 2013;Solas et al 2013;Milano et al 2014). Consequently, patterns of abalone larval settlement and establishment could be determined by underlying adaptive genetic variation, where recruitment at the reef scale is dependent on the settlement of compatible adaptive genotypes.…”
Section: Factors Influencing Larval Movement and Recruitmentmentioning
confidence: 99%
“…Additionally, adaptive genetic divergences among populations, particularly on finer spatial scales, can assist in deciphering the influence of natural selection on recruitment processes (Marshall, Monro, Bode, Keough, & Swearer, ). Studies on marine fish and invertebrates have demonstrated that adaptive variation can be maintained despite high levels of gene flow (Galindo et al, ; Hess et al, ; Martinez‐Fernandez, Bernatchez, Rolan‐Alvarez, & Quesada, ; Milano et al, ; Sandoval‐Castillo, Robinson, Hart, Strain, & Beheregaray, ; Solas, Sepulveda, & Brante, ), suggesting that selection can influence recruitment processes as some potential recruits are expected to be maladapted to certain habitat types (Marshall et al, ). Information on gene flow and population connectivity informs whether populations can replenish naturally following disturbance and depletion, and when management intervention is required (Whiterod, Zukowski, Asmus, Gilligan, & Miller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Immune gene expression is a commonly used measure of immune traits. Immune gene expression is known to differ among host populations (Jeukens et al 2009;Lenz et al 2013;Martinez-Fernandez et al 2010;McCairns & Bernatchez 2010;Morris et al 2014). Immune gene expression influences host resistance to parasite infection in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%